Answer:
3cm espero te sirva jajajajaja
The series of numbers is adding 5 and then subtracting 2
20+5=25
25-2=23
23+5=28
28-2=26
and so on. Do you understand?
Answer:
Step-by-step explanation:
Hello, please consider the following.
![3\cdot 4^n+51=3\cdot 4^n+3\cdot 17=3(4^n+17)](https://tex.z-dn.net/?f=3%5Ccdot%204%5En%2B51%3D3%5Ccdot%204%5En%2B3%5Ccdot%2017%3D3%284%5En%2B17%29)
So this is divisible by 3.
Now, to prove that this is divisible by 9 = 3*3 we need to prove that
is divisible by 3. We will prove it by induction.
Step 1 - for n = 1
4+17=21= 3*7 this is true
Step 2 - we assume this is true for k so
is divisible by 3
and we check what happens for k+1
![4^{k+1}+17=4\cdot 4^k+17=3\cdot 4^k + 4^k+17](https://tex.z-dn.net/?f=4%5E%7Bk%2B1%7D%2B17%3D4%5Ccdot%204%5Ek%2B17%3D3%5Ccdot%204%5Ek%20%2B%204%5Ek%2B17)
is divisible by 3 and
is divisible by 3, by induction hypothesis
So, the sum is divisible by 3.
Step 3 - Conclusion
We just prove that
is divisible by 3 for all positive integers n.
Thanks
Answer:
Step-by-step explanation:
This was answered in question #24217201. It's the exact same question, but you forgot to put what parts A and B are. The answers and the work are there.
Answer:
No she is wrong.
Step-by-step explanation:
Let's simplify step-by-step.
6−3y+4+2y
=6+−3y+4+2y
Combine Like Terms:
=6+−3y+4+2y
=(−3y+2y)+(6+4)
=−y+10
Answer:
=−y+10